Linguistic Landscape of Food Stall and Restaurant Names: A Supply Chain Management of Halal Food in Malang City, Indonesia - Sumarlam Sumarlam; Dwi Purnanto; Dany Ardhian (International Journal of Supply Chain Management, 2020)
Abstract-In a country with a majority Muslim population, increase in economy, purchasing power and consumption such as Indonesia, halal food is a principal requirement. This has led to the springing of certified and uncertified halal food stalls in their supply chain. Therefore, this study aims to observe the supply chains used in naming halal food stalls and restaurants and how its distribution chain is applied to its certification in Indonesia through the official government agencies. The research data consists of 503 names of food stalls and restaurants in five districts of Malang City, namely, Klojen, Lowokwaru, Blimbing, Sukun, and Kedungkandang.  Furthermore, photography techniques and several applications such as MUI Halal, Halal Tracking, and Kuliner Malang are used to provide information and validation of halal certificates. Data was analyzed using Linguistic Landscape design on the frequency of language use, its monolingual and bilingual forms, as well as the information and symbolic functions. The results showed that monolingual and bilingual Indonesian languages, English, and Javanese were dominantly used compared to Japanese, Chinese, Arabic, and Dutch. Therefore, the perceptions of nationalism, internationalism, Javanism, and Islamism are instilled, though the official halal certificates still show a slight number.